LECANDUS study (LEsion CANdidate Detection in UltraSound Data): evaluation of image analysis algorithms for breast lesion detection in volume ultrasound data - Golatta, Michael; Zeegers, Désirée; Filippatos, Konstantinos; Binder, Leah-Larissa; Scharf, Alexander; Rauch, Geraldine; Rom, Joachim; Schütz, Florian; Sohn, Christof; Heil, Jörg (Archives of gynecology and obstetrics, 2016)
This study aims at developing and evaluating a prototype of a lesion candidate detection algorithm for a 3D-US computer-aided diagnosis (CAD) system.
Gesehen am 30.06.2020